(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
water springs can be researched like the objects of geo heritage, geo diversity, geo tops, nature, drinking water resources, mythology, tourism objects and others. They are important from the scientific, aesthetic, tourism, and cultural points of view. This article aims to analyse water springs as geo tops, geo heritage and drinking water resources. The content of water’s chemical structure, cations and anions in spring water will be taken into account. After the water quality analysis in Utena district was made, it was set that the prevailing springs’ water is slightly alkaline hard water of relatively low conductivity. The prevailing anions are hydrocarbonates, and the prevailing cations – calcium, sodium, magnesium. The amount of the nitrates does not exceed the limits.